Diffuse subcortical white matter injury and bilateral basal ganglia neuronal loss after acute opioid overdose. Issue 3 (June 2020) - Dinicu, Andreea I; Chaudhari, Amit; Kayyal, Simon
Opiate intoxication has been associated with life-threatening effects of sympathetic suppression and respiratory depression, but current literature is limited in describing its neurotoxic effects on the central nervous system. Here, we present the case of an otherwise high-functioning adolescent male who was found unresponsive after ingestion of approximately 3–4 fake oxycodone 10–325 mg pills laced with fentanyl. Magnetic resonance imaging showed evidence of diffuse T2 hyperintensities in the corpus callosum and bilateral frontal, parietal, and cerebellum indicative of diffuse white matter injury. In addition, there were distinct areas of restricted diffusion in the bilateral basal ganglia concerning for oxidative stress-mediated neuronal loss. His neurological exam improved with supportive treatment over the course of his hospitalization. Although limited literature has shown leukoencephalopathy to be associated with opioid overdose, we present a case of additional involvement of subcortical gray matter.